2002
DOI: 10.1002/cncr.11055
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin and meglumine γ‐linolenic acid

Abstract: BACKGROUND Anthracyclines have been established as first‐line drugs for intravesical use in the treatment of patients with superficial bladder carcinoma, although they result only in a modest reduction in tumor recurrence rates. The essential fatty acid γ‐linolenic acid (GLA) also is an effective cytotoxic agent against superficial bladder carcinoma when it is applied topically. The objective of this study was to assess the efficacy of combined epirubicin and GLA with the purpose of developing a suitable model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Spontaneously fluorescent epirubicin was used to examine epirubicine uptake (12,13). Forty-eight hours after siRNA transfection, 3 ϫ 10 5 cells were trypsinized and resuspended in 1 ml of medium containing 1 M Oregon Green paclitaxel or 16 M epirubicin and incubated for 20, 50, or 80 min T, paclitaxel; FAC, 5-flurouracil, doxorubicin, and cyclophosphamide.…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneously fluorescent epirubicin was used to examine epirubicine uptake (12,13). Forty-eight hours after siRNA transfection, 3 ϫ 10 5 cells were trypsinized and resuspended in 1 ml of medium containing 1 M Oregon Green paclitaxel or 16 M epirubicin and incubated for 20, 50, or 80 min T, paclitaxel; FAC, 5-flurouracil, doxorubicin, and cyclophosphamide.…”
Section: Methodsmentioning
confidence: 99%
“…The capacity of GLA to enhance the activity of various pharmaceutical preparations against cancer cells has been previously described . GLA itself was found to induce apoptosis on HL‐60 cells and to be toxic on human leukemic K562 cells, especially in high concentrations .…”
Section: Discussionmentioning
confidence: 92%
“…reported that lithium or meglumine GLA salts may exert a direct antiproliferative activity on human glioblastoma cell lines . This fatty acid was shown to enhance epirubicin efficacy on human urothelial cancer cells and tamoxifen activity in breast cancer patients , while it exerted synergistic activity with vinorelbine against breast cancer cells and amplified the sensitivity of leukemic cells to doxorubicin, etoposide, and vincristine . It seems that the growth inhibitory effect of lithium GLA on pancreatic cancer cell lines was enhanced by ferric ions but repressed by albumin .…”
Section: Introductionmentioning
confidence: 99%
“…GLA is also sometimes promoted as an anti-cancer agent. Neither GLA nor other GLA-rich supplements have been convincingly shown to be useful in preventing or treating any other health conditions [32,33,34,35]. 9-octadecynoic acid (oleic acid) is the most abundant fatty acid in human adipose tissue [36], and second in abundance in human tissues overall only to palmitic acid [37].…”
Section: Resultsmentioning
confidence: 99%